Vochysia sobralii (Vochysiaceae), a new species from Serra do Cachimbo, Pará, Brazil, and updated keys for Vochysia sect. Pachyantha - Shimizu, Gustavo Hiroaki; Gonçalves, Deise Josely Pereira (Phytotaxa, 2022)
Vochysia sobralii, a new species of Vochysiaceae endemic to the Serra do Cachimbo, in the state of Pará, Brazil, is described and illustrated in this study. The newly described species is included in Vochysia section Pachyantha, which comprises species with tomentose ovary and without petals. Additionally, two updated identification keys (one dichotomous and other multi-access interactive) for V. sect. Pachyantha, with all ten species, are provided.